Scandinavia in the middle ages 900-1550 - Salonen, Kirsi, author.
1 online resource
Keywords: "Scandinavia went through momentous changes throughout the Middle Ages, emerging out of the Viking and Norse age towards 'Christianization'. Alongside this came social, economic and cultural changes which completely transformed the region into the kingdoms which existed in the Early Modern Period. Scandinavia in the Middle Ages covers the entire Middle Ages and integrates all areas of Scandinavia political, religious, cultural and social history into a coherent analysis. Within the broader narrative the historiography of the period and specific topics such as Norse literature, runes and neglected topics such as minorities, like the Sami and Jews, are discussed. Each chapter includes numerous textboxes, which explore central themes, persons and events in greater detail, ensuring students can quickly gauge the key information. The book is divided into three chronological parts 900-1200, 1200-1400 and 1400-1550, which guides the reader through the period in easily digestible sections. This book is essential reading for students of, as well as all those interested in, medieval Scandinavia and Europe more broadly"--